Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - Chapter 11 Review Problem Set: 64


{$\frac{-1 - i\sqrt {59}}{6},\frac{-1 + i\sqrt {59}}{6}$}

Work Step by Step

Step 1: Comparing $3x^{2}+x+5=0$ to the standard form of a quadratic equation, $ax^{2}+bx+c=0$, we find: $a=3$, $b=1$ and $c=5$ Step 2: The quadratic formula is: $x=\frac{-b \pm \sqrt {b^{2}-4ac}}{2a}$ Step 3: Substituting the values of a, b and c in the formula: $x=\frac{-(1) \pm \sqrt {(1)^{2}-4(3)(5)}}{2(3)}$ Step 4: $x=\frac{-1 \pm \sqrt {1-60}}{6}$ Step 5: $x=\frac{-1 \pm \sqrt {-59}}{6}$ Step 6: $x=\frac{-1 \pm \sqrt {-1\times59}}{6}$ Step 7: $x=\frac{-1 \pm (\sqrt {-1}\times\sqrt {59})}{6}$ Step 8: $x=\frac{-1 \pm (i\times \sqrt {59})}{6}$ Step 9: $x=\frac{-1 \pm i\sqrt {59}}{6}$ Step 10: $x=\frac{-1 - i\sqrt {59}}{6}$ or $x=\frac{-1 + i\sqrt {59}}{6}$ Step 11: Therefore, the solution set is {$\frac{-1 - i\sqrt {59}}{6},\frac{-1 + i\sqrt {59}}{6}$}.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.